Sosialisasi Penggunaan Peanut Ball untuk Mengurangi Nyeri Persalinan Kala 1 di Desa Moncongloe Bulu Kabupaten Maros - Nurjannah Supardi (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2022)
In order to improve the community development business system to be more productive and efficient, technology is needed. The introduction of technology that has developed in society is technology that has been developed in a modern way, or what is known as "appropriate technology" or technology and its applications that have the characteristics of decentralization, relatively small scale, labor intensive, energy efficient and closely related to local conditions. The growth and development of technology is determined by the conditions and level of isolation and openness of the community as well as the level of growth of the socio-economic life of the community. To introduce appropriate technology, it needs to be adapted to the needs, namely the needs that are oriented to such conditions, which are new goods for the community and need to be utilized and known by the community about its value and usefulness. The technology used can vary, in this counseling peanut ball was chosen as a medium to reduce labor pain in the first stage. It is hoped that after attending this counseling, pregnant women can find out how to reduce pain when facing the first stage so that they can be calmer in the process. later delivery.